Comparison of erectile function in patients with end‐stage renal disease receiving haemodialysis and kidney transplantation. (2nd April 2021) - Kaya, Bulent; Deger, Mutlu; Paydas, Saime; Akdogan, Nebil; Altun, Eda; Kayar, Erkan; Yucel, Sevinc Puren; Balal, Mustafa
Abstract: To investigate the frequency and risk factors of ED in haemodialysis patients (HDps) and kidney transplantation (KTx) recipients (KTxRs). HDps and KTxRs between the ages of 18–65 were compared in terms of ED. IEFF‐15 (International Index of Erectile Function) score was used to evaluation of ED. Fifty‐seven male HDps and 52 male KTxRs with a mean age of 45.6 ± 10.4 years were included in our study. DM, CAD, hyperlipidaemia, smoking and beta blocker use were higher HDps ( p  = 0.037, p  < 0.001, p  = 0.001, p  = 0.001 and p  = 0.031 respectively). There was no ED in five (8.8%) HDps and 27(51.9%) KTxRx. Severity of ED was significantly higher in HDps ( p  < 0.001). In multiple logistic regression analysis, KTx was found the most relevant associated factor with ED. KTxRs had decreased risk for ED (OR = 0.09, 95% CI 0.02–0.30, p  < 0.001). ED is significantly more common in HDps than KTxRs. Known risk factors for ED, HT, DM, CAD, HL, smoking, obesity and beta‐blocker use were not related to ED in the HDps and KTxRs, and the KTx was positively effective for ED in patients undergoing renal replacement therapy.